The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpsyg.2020.01008
|View full text |Cite
|
Sign up to set email alerts
|

Well Done! Effects of Positive Feedback on Perceived Self-Efficacy, Flow and Performance in a Mental Arithmetic Task

Abstract: Self-efficacy is a well-known psychological resource, being positively associated with increased performance. Furthermore, results from field studies suggest a positive impact of self-efficacy on flow experience, which has not yet been tested experimentally. In this study, we manipulated self-efficacy by means of positive feedback and investigated whether self-efficacy serves as a mediator in the relationship between positive feedback and flow and in the relationship between positive feedback and performance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 79 publications
3
22
0
1
Order By: Relevance
“…Strategies proposed by Bakker and van Woerkom (2017) such as job crafting, playful work design, and strengths use should also be examined in future studies. Other potential strategies include positive feedback (Peifer, Schönfeld, Schönfeld, Wolters, Aust, & Margraf, 2020) and mindfulness (Weintraub & Dust, 2020) interventions should be tested in easily implemented field studies. Additionally, while the goal‐setting nudge was supported as an effective intervention, there is potential for improving this strategy in future research as well.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies proposed by Bakker and van Woerkom (2017) such as job crafting, playful work design, and strengths use should also be examined in future studies. Other potential strategies include positive feedback (Peifer, Schönfeld, Schönfeld, Wolters, Aust, & Margraf, 2020) and mindfulness (Weintraub & Dust, 2020) interventions should be tested in easily implemented field studies. Additionally, while the goal‐setting nudge was supported as an effective intervention, there is potential for improving this strategy in future research as well.…”
Section: Discussionmentioning
confidence: 99%
“…Studies that implemented normative feedback administered various kinds of cognitive tasks (e.g., arithmetic tasks, name recall). They demonstrated that participants who received positive normative feedback reported higher self-efficacy and performed better compared to those who did not receive feedback [ 18 , 19 ]. These results seem to suggest that fictitious positive normative feedback is an effective intervention to promote self-efficacy [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that participants who received positive normative feedback reported higher self-efficacy and performed better compared to those who did not receive feedback [ 18 , 19 ]. These results seem to suggest that fictitious positive normative feedback is an effective intervention to promote self-efficacy [ 18 ]. However, to our knowledge, no studies have manipulated self-efficacy in the spatial cognition domain.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations